The Italian Catquest-9SF cataract questionnaire: translation, validation and application - Skiadaresi, Eirini (Eye Vis (Lond), 2016)
BACKGROUND: To validate the Catquest-9SF questionnaire in Italian, assess the change in visual disability with cataract surgery and determine the correlation between pre-operative Catquest-9SF scores and Lens Opacities Classification System (LOCS) III cataract grading. METHODS: Prospective, questionnaire validation study. The Catquest-9SF questionnaire was forward and back translated and completed by 209 Italian patients before and three months following cataract surgery. Rasch analysis was used to assess its psychometric properties. RESULTS: The Italian Catquest-9SF demonstrated ordered response categories, unidimensionality (item fit statistics range: 0.73–1.34), adequate person separation (2.04), and no differential item functioning. Mistargeting was evident with a mean difference in item difficulty and person ability of 2.04 logits but improved with inclusion of pre-operative data only. There was a statistically significant (Friedman tests, p < 0.001) median improvement in visual disability of 1.92, 3.57, 1.44 and 2.94 logits in patients undergoing first eye surgery with and without ocular comorbidity, and second eye surgery with and without ocular comorbidity respectively. There was no statistically significant difference in the improvements among the four groups (Kruskal-Wallis H test, X(2)(3) = 5.445, p = 0.142). There was no correlation between Catquest-9SF scores and nuclear opalescence (r(s) = 0.049, p = 0.478), nuclear colour (r(s) = 0.008, p = 0.909), cortical (r(s) = 0.066, p = 0.341), and posterior subcapsular components (r(s) = 0.048, p = 0.494). CONCLUSIONS: The Italian Catquest-9SF demonstrated good psychometric properties and is suitable for use in Italian speaking patients. There were similar improvements in visual disability in patients undergoing first or second eye surgery, with or without ocular comorbidity. There was no correlation between pre-operative Catquest-9SF scores and LOCS III cataract grading.